2017
DOI: 10.1111/jan.13410
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance, anorexia nervosa and the inpatient setting: A mixed methods study

Abstract: Nurses' capacity for developing therapeutic alliances is in part dependent on a supportive ward organization and the adequacy of resources to permit meaningful interactions with consumers with anorexia nervosa. Understanding the contextual factors specific to the inpatient setting enhances nurses' ability to develop therapeutic alliances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…The systemic pressure of lack of time seemed to be felt most keenly in primary care, while the surveillance culture and frustrations around communication were predominantly reported in inpatient settings. The greater likelihood that nurses would engage in avoidance and blame, and adopt a maternal stance, may reflect their high level of contact with people with EDs and their involvement in implementing treatment protocols, positioning them both for intimacy with service users and becoming the object of their anger (Ryan et al, ; Zugai et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systemic pressure of lack of time seemed to be felt most keenly in primary care, while the surveillance culture and frustrations around communication were predominantly reported in inpatient settings. The greater likelihood that nurses would engage in avoidance and blame, and adopt a maternal stance, may reflect their high level of contact with people with EDs and their involvement in implementing treatment protocols, positioning them both for intimacy with service users and becoming the object of their anger (Ryan et al, ; Zugai et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The greater likelihood that nurses would engage in avoidance and blame, and adopt a maternal stance, may reflect their high level of contact with people with EDs and their involvement in implementing treatment protocols, positioning them both for intimacy with service users and becoming the object of their anger (Ryan et al, 2006;Zugai et al, 2018aZugai et al, , 2018b. Fox et al (2012) highlighted the irony that it is generally the least experienced HCPs who spend most time with service users and receive the least containment in the form of space to formulate, process, and reflect.…”
Section: Discussionmentioning
confidence: 99%
“…Consumers’ open opposition towards nurses is likely a manifestation of the distress that consumers experience from re‐feeding and weight gain (Zugai et al . ), and also may be an overt attempt to re‐establish power. Some nurses in this study felt uncomfortable with exercising their authority, due to the opposition that they were liable to receive.…”
Section: Discussionmentioning
confidence: 99%
“…This paper reports on a subset of data from a larger study reported elsewhere (Zugai et al . ,). Data for this study were collected between May 2014 and February 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation